Reinforcing the Concept of Calculating Isotope Pattern Using Theoretical Isotope Generator (TIG) - Kamalrudin, M.; Soong, Hoong Cheng; Abdul-Aziz, Azlianor; Sulong, Muhammad Suhaizan (World Scientific and Engineering Academy and Society (WSEAS), 2008)
This paper describes how the isotope patterns are calculated for chemists, students, lecturers and researchers using Theoretical Isotope Generator (TIG) integrated from the .NET framework (specifically VB.NET) with the data from the dual databases (Microsoft Access and Microsoft SQL 2000). Accordingly, TIG in terms of its functionality and features is an application developed to gain related information on molecules and their relative intensity for educational purposes (chemists, students, lecturers and researchers). Although various mass spectrometer applications are available as web-based and windows-based systems, the projected software is indeed practical, beneficial and constructive for the academic learners as well for the intellectual researchers for rapidly defining the numbers of the possibility isotope patterns obtainable from a substance(chemical compound) for example methane (CH2). Therefore, TIG with the mathematical application called Cartesian Products is used to obtain the isotope patterns of any atom or molecules. TIG provides extra features than others that are proficient to retrieve the information of the mass (atomic/molecular weight) from the substance specified based from the isotope patterns available. Additionally, TIG is completely with several functionalities such as drawing, normalizing and zooming the generated graph that convey with the molecular information in a number of formats by providing the details of the calculation and molecules.